A Comparative Analysis of Traditional and Smart Prosthetic Sockets: Enhancing Gait Symmetry and User Comfort - Nasir, Shahed S.; Aboud, Wajdi Sadik; Haris, Sallehuddin Mohamed (Al-Nahrain Journal for Engineering Sciences, 2025)
This study compares two different sockets, traditional and smart. It includes designs, manufacturing, and testing to evaluate the influence of the socket designs on gait symmetry. The proposed materials are locally available in the prosthetics center where traditional sockets are manufactured. and smart socket designs with the same materials as traditional additions. A simple electronic system programmed to control the movement of the stump by pneumatic pads and prevent slipping during movement is considered an advanced suspension system. A gait cycle test was carried out to evaluate the sockets. it was performed on a patient with AK amputation in two cases: the first when the patient was wearing the traditional and the second when wearing the smart. Where the difference in (gait cycle time, step velocity, heel contact, and mid-stance) between the left and right leg is equal to (0.54, 4.3, 0.19, and 0.34) respectively, when the patient uses the traditional, while these values reduce to (0.09, 0.7, 0.07, and 0.27) respectively when the patient used the smart, it improves comfort by modifying pressure distribution, relieving pressure points, and enhancing functionality through gait analysis. They adjust to the volume of the residual limb, ensuring an effective fit. Real-time monitoring and remote modifications decrease the need for in-person meetings and enhance user confidence. The smart socket, designed to fit user requirements, provides enhanced comfort, functionality, and independence. The studies will explore its long-term benefits and broader applications, focusing on its originality, practical implications, and outcome measurement.